2015
DOI: 10.1128/jcm.00795-15
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Microplate-Based Growth Assay for Determination of Antifungal Susceptibility of Histoplasma capsulatum Yeasts

Abstract: bStandardized methodologies for determining the antifungal susceptibility of fungal pathogens is central to the clinical management of invasive fungal disease. Yeast-form fungi can be tested using broth macrodilution and microdilution assays. Reference procedures exist for Candida species and Cryptococcus yeasts; however, no standardized methods have been developed for testing the antifungal susceptibility of yeast forms of the dimorphic systemic fungal pathogens. For the dimorphic fungal pathogen Histoplasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 44 publications
3
41
0
1
Order By: Relevance
“…This confirms the findings of an earlier antifungal susceptibility study of six E. africanus yeast phase isolates (5). There are no well-standardized methods for MIC determination for thermally dimorphic fungi (19); nevertheless, in vitro activities of polyenes (i.e., amphotericin B), azoles, and echinocandins have been established for some of these organisms (20). We used Clinical and Laboratory Standards Institute (CLSI)-approved standards as a guide to yeast and mold phase testing but used a larger inoculum for the mold phase and a prolonged incubation period to facilitate growth and endpoint determinations, in line with previous studies (5,19,(21)(22)(23).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This confirms the findings of an earlier antifungal susceptibility study of six E. africanus yeast phase isolates (5). There are no well-standardized methods for MIC determination for thermally dimorphic fungi (19); nevertheless, in vitro activities of polyenes (i.e., amphotericin B), azoles, and echinocandins have been established for some of these organisms (20). We used Clinical and Laboratory Standards Institute (CLSI)-approved standards as a guide to yeast and mold phase testing but used a larger inoculum for the mold phase and a prolonged incubation period to facilitate growth and endpoint determinations, in line with previous studies (5,19,(21)(22)(23).…”
Section: Discussionsupporting
confidence: 80%
“…There are no well-standardized methods for MIC determination for thermally dimorphic fungi (19); nevertheless, in vitro activities of polyenes (i.e., amphotericin B), azoles, and echinocandins have been established for some of these organisms (20). We used Clinical and Laboratory Standards Institute (CLSI)-approved standards as a guide to yeast and mold phase testing but used a larger inoculum for the mold phase and a prolonged incubation period to facilitate growth and endpoint determinations, in line with previous studies (5,19,(21)(22)(23). Antifungal susceptibility testing for thermally dimorphic fungi is often limited to the mold phase, results of which may be misleading because the yeast phase is responsible for human disease (20).…”
Section: Discussionmentioning
confidence: 99%
“…This is not an insignificant question as the yeast and hyphal forms of the dimorphic fungi can have dramatically different susceptibilities. [62][63][64][65][66][67][68][69] For example, early studies with echinocandins showed antifungal effects on the hyphal form of Histoplasma. 67 However, subsequent tests against the yeast form indicated that caspofungin was anywhere from 20-to 1000-fold less effective.…”
Section: Current Antifungal Optionsmentioning
confidence: 99%
“…Cell Wall Sensitivity Assays-Yeast cells were grown in 96-well microtiter plates (38) with graded concentrations of antifungal compounds (fluconazole (Glenmark Generics); caspofungin (Merck); and nikkomycin Z (gift from John Galgiani)) and cell wall-destabilizing compounds (Calcofluor White (Sigma); Congo red (MP Biomedicals); SDS; and Uvitex) (39). Growth after 4 days was measured by optical density at 595 nm and compared with the turbidity of wells lacking inhibitors.…”
mentioning
confidence: 99%